2022
DOI: 10.48550/arxiv.2201.08858
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The size-luminosity relation of lensed galaxies at $z=6-9$ in the Hubble Frontier Fields

Lilan Yang,
Nicha Leethochawalit,
Tommaso Treu
et al.

Abstract: We measure the size-luminosity relation of photometrically-selected galaxies within the redshift range 𝑧 ∼ 6 − 9, using galaxies lensed by six foreground Hubble Frontier Fields (HFF) clusters. The power afforded by strong gravitational lensing allows us to observe fainter and smaller galaxies than in blank fields. We select our sample of galaxies and obtain their properties, e.g., redshift, magnitude, from the photometrically-derived ASTRODEEP catalogues. The intrinsic size is measured with the Lenstruction s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 60 publications
(77 reference statements)
0
5
0
Order By: Relevance
“…Such a dependence is expected in the case of an especially steep sizeluminosity relation for z ∼ 2-9 galaxies, i.e., where r ∝ L 0.5 and there is no change in the surface brightness of sources versus luminosity or magnification factor at the faint end of the HFF probes. Interestingly enough, Bouwens et al (2017aBouwens et al ( , 2021a, Kawamata et al (2018), andYang et al (2022) all found steep size-luminosity relations at z  6, with radius depending on luminosity as L 0.50±0.07 , -+ L 0.46 0.09 0.08 , L 0.40±0.04 , and L 0.48±0.08 . As important context, a negative δ would be expected for the size-luminosity relations derived for brighter field galaxies in the intermediate-or high-redshift universe.…”
Section: Implications For the Selection Efficienciesmentioning
confidence: 94%
“…Such a dependence is expected in the case of an especially steep sizeluminosity relation for z ∼ 2-9 galaxies, i.e., where r ∝ L 0.5 and there is no change in the surface brightness of sources versus luminosity or magnification factor at the faint end of the HFF probes. Interestingly enough, Bouwens et al (2017aBouwens et al ( , 2021a, Kawamata et al (2018), andYang et al (2022) all found steep size-luminosity relations at z  6, with radius depending on luminosity as L 0.50±0.07 , -+ L 0.46 0.09 0.08 , L 0.40±0.04 , and L 0.48±0.08 . As important context, a negative δ would be expected for the size-luminosity relations derived for brighter field galaxies in the intermediate-or high-redshift universe.…”
Section: Implications For the Selection Efficienciesmentioning
confidence: 94%
“…The negative gradient in the intrinsic size-luminosity relation presented in Figure 5 is in direct conflict with observational results which necessarily include the effects of dust attenuation (e.g. Hathi et al 2008;Grazian et al 2011Grazian et al , 2012Shibuya et al 2015;Calvi et al 2016;Kawamata et al 2015Kawamata et al , 2018Morishita et al 2018;Bridge et al 2019;Bouwens et al 2021;Yang et al 2022). However, in Section 5.2.1 we have shown that the inclusion of dust attenuation can result in large increases in size for the most intrinsically compact galaxies.…”
Section: The Observed Uv Size-luminosity Distributionmentioning
confidence: 59%
“…Figure 9 shows a comparison of these fits (solid red lines) to fits from observed samples: Huang et al (2013) at 𝑧 = 5, Holwerda et al (2015) at 𝑧 = 7 and 𝑧 = 9, Kawamata et al (2018) at 𝑧 = 6 − 9, Bouwens et al (2021) at 𝑧 = 6 − 8, and Yang et al (2022) at 𝑧 = 6 − 7, the latter 3 of these including lensed sources. We also compare to two simulations: the M semi-analytic model (Liu et al 2016;Marshall et al 2019) at 𝑧 = 5 − 9, and the B T simulation (Marshall et al 2021) at 𝑧 = 7 − 9.…”
Section: The Observed Uv Size-luminosity Distributionmentioning
confidence: 99%
See 2 more Smart Citations